Managerial preferences in relation to financial indicators regarding the mitigation of global change - Maroušek, Josef; Hašková, Simona; Zeman, Robert; Vaníčková, Radka (Science and engineering ethics, 2015)
Biochar is a soil-improving substrate made from phytomass pyrolysis. In Southeast Asia, its application decreases due to the long-term growth of biochar cost and thus caused further prolongation of the payback period. In the Euro-American civilization the biochar application is already almost forgotten once it has been much earlier recognized that the crop yields can be increased much faster with higher doses of nutrients and other agrochemicals. The payback period can be expected in decades. Such a long-time investment into soil fertility raises also many ethical questions. The final decision combines issues of social responsibility, risk and other financial indicators as well as personal preferences and more. The attitudes of Western and Central European decision makers in the agriculture business segment were analyzed on the basis of electronic questionnaire survey and a subsequent interview through their local unions. According to the data, most of them did not know about the possibilities of a more environmentally friendly approach to soil enhancement based on the addition of a fertilizer in the form of biochar. Among others, the collected data also shows that the decision makers from Western Europe have a much different ethical approach to the land and financial indicators than the Central Europeans.
Keywords: průmyslová hnojiva; Climate Change; Europe; Agriculture; obchod; Evropa; zemědělství; průzkumy a dotazníky; klimatické změny; Commerce; náklady a analýza nákladů; Humans; Soil; Fertilizers; dřevěné a živočišné uhlí; Surveys and Questionnaires; Environment; Charcoal; životní prostředí; Costs and Cost Analysis; půda; lidé